Vestnorden. A functional region? - Grétar Þór Eyþórsson 1959-; Hovgaard, Gestur (2013)
Fræðigrein This article discusses the issue of what kind of a region Vestnorden is. The need for such a discussion arises from the challenges posed by globalisation for the idea and construction of the West Nordic space, and the need to observe how this regional unit counters these processes. The article is based on an analytical framework which presupposes that a functional region has to consist of four elements. First, whether the space has its own institutions for decision making; second, how far there is economic complementarities among the involved nations and territories; third, to what degree they have common economic interests; and finally, to what extent social, cultural and historical ties exist between the territories involved. The article argues that there is an urgent need to discuss and reorient the institutional functionality of Vestnorden as a regional unit.